European Menopause and Andropause Society (EMAS) and International Gynecologic Cancer Society (IGCS) position statement on managing the menopause after gynecological cancer: focus on menopausal symptoms and osteoporosis. (April 2020) - Rees, Margaret; Angioli, Roberto; Coleman, Robert L.; Glasspool, Rosalind; Plotti, Francesco; Simoncini, Tommaso; Terranova, Corrado
Highlights: Worldwide, it is estimated that about 1.3 million new gynecological cancer cases are diagnosed each year. Management of menopausal symptoms and the prevention and treatment of osteoporosis in women with gynecological cancer needs to be individualized, with or without menopausal hormone therapy, according to tumor type and stage, and the woman's age. In women who are taking anti-estrogenic therapies such as aromatase inhibitors, estrogen-based therapies are contraindicated and non-hormonal options are recommended as initial therapy. Abstract: Introduction: Worldwide, it is estimated that about 1.3 million new gynecological cancer cases are diagnosed each year. For 2018, the predicted annual totals were cervix uteri 569, 847, corpus uteri 382, 069, ovary 295, 414, vulva 44, 235 and va​gina 17, 600. Treatments include hysterectomy with or without bilateral salpingo-oophorectomy, radiotherapy and chemotherapy. These can result in loss of ovarian function and, in women under the age of 45, early menopause. Aim: The aim of this position statement is to set out an individualized approach to the management, with or without menopausal hormone therapy, of menopausal symptoms and the prevention and treatment of osteoporosis in women with gynecological cancer. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: The limited data suggest that women with low-grade, early-stage endometrial cancer may consider systemic or topical estrogens. However, menopausal hormone therapy may stimulate tumor growth in patients with more advanced disease, and non-hormonal approaches are recommended. Uterine sarcomas may be hormone dependent, and therefore estrogen and progesterone receptor testing should be undertaken to guide decisions as to whether menopausal hormone therapy or non-hormonal strategies should be used. The limited evidence available suggests that menopausal hormone therapy, either systemic or topical, does not appear to be associated with harm and does not decrease overall or disease-free survival in women with non-serous epithelial ovarian cancer and germ cell tumors. Caution is required with both systemic and topical menopausal hormone therapy in women with serous and granulosa cell tumors because of their hormone dependence, and non-hormonal options are recommended as initial therapy. There is no evidence to contraindicate the use of systemic or topical menopausal hormone therapy by women with cervical, vaginal or vulvar cancer, as these tumors are not considered to be hormone dependent.